E.T.A. Hoffmann's opera manifesto: romantic philosophy and musical semantics in early German Romantic opera - Boucher, Daniel (2020)
In the wide array of scholarship on music and Romanticism, in-depth studies on early German Romantic opera remain limited. Those that do exist are often characterised by the troubles surrounding its development in comparison to the international success of Italian and French opera (Meyer, 2003; Markx, 2016). Despite a flourishing of German opera in the early nineteenth century, questions remain surrounding what stimulated this sudden profusion and how the works of this period laid the foundations for later figures such as Wagner. In order to achieve a better understanding of early German Romantic opera, I have chosen to explore E. T. A. Hoffmann’s literary output in the Allgemeine musikalische Zeitung. Through four publications – 'Ritter Gluck' (1809), 'Don Juan' (1813), 'Der Dichter und der Komponist' (1813), and 'Kreisleriana' (1814) – Hoffmann explored what he believed to be a true Romantic opera, creating what I will call an opera manifesto. This thesis explores how the ideas Hoffmann presented in his manifesto underpin and unite milestones in early German Romantic opera. Grounded in contemporary Romantic philosophy, his ideas contributed to the formation of a national style. Specifically, I will show how his radical aesthetics encouraged composers to use the orchestra as an agent to express the drama, as well as to convey the Romantic quest for the Absolute. To demonstrate how Hoffmann’s ideas were realised, I will consider musical semantics in Weber’s 'Der Freischütz' (1821), Marschner’s 'Der Vampyr' (1828), and Wagner’s 'Die Feen' (1834). I will explore how these three composers used a range of signifiers, including musical topics and symbols, key associations, and diegetic music, to denote different aspects of the drama through the voice of the orchestra. This thesis also demonstrates how Hoffmann’s literary output laid important foundations for Wagner’s own aesthetics of opera, thereby showing how Hoffmann’s influence is traceable throughout the nineteenth century.